1990
DOI: 10.1136/gut.31.9.1006
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypervolaemia increases gastroduodenal resistance to the flow of liquid in the rat.

Abstract: The effect of volume expansion of extracellular fluid on gastroduodenal resistance to the flow of isotonic saline was assessed in three groups of rats using intravenous infusions of isotonic, isotonic-isoncotic, and isotonicisoncotic-isohaemic solutions. The gastroduodenal segment of 29 male Wistar rats was barostatically perfused at a constant pressure gradient of 4 cm H20 and changes in flow (ml/ minute) were taken as a reflection of changes in gastroduodenal resistance. Isotonic expansion led to a 33% drop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 16 publications
2
29
2
Order By: Relevance
“…This appears to be a more reasonable explanation since it is supported by our previous studies (4,5,7,8), and reinforced by a recent observation that duodenal motility is increased by BV expansion in anesthetized dogs (7). We have also verified that the gastric fundus, as well as the duodenum may actively participate in the GE delay due to BV expansion (8,9), but the possible pyloric participation cannot be completely excluded (8,9).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This appears to be a more reasonable explanation since it is supported by our previous studies (4,5,7,8), and reinforced by a recent observation that duodenal motility is increased by BV expansion in anesthetized dogs (7). We have also verified that the gastric fundus, as well as the duodenum may actively participate in the GE delay due to BV expansion (8,9), but the possible pyloric participation cannot be completely excluded (8,9).…”
Section: Discussionsupporting
confidence: 83%
“…Firstly, we have observed that gastric and jejunal compliances are decreased by BV expansion while they are increased by BV retraction in anesthetized dogs (2,3). In addition, utilizing a barostatically perfused system, we have observed that BV changes also modify the gastroduodenal resistance to saline flow in anesthetized dogs: BV expansion increases the resistance of the gastroduodenal segment to the flow of liquid while retraction decreases it (4,5,8).…”
Section: Introductionmentioning
confidence: 97%
“…Gastrointestinal motor and absorptive functions and extracellular fluid volume are tightly interlinked, and changes in blood volume may accordingly modify gastroduodenal flow (15,16). Experimental hypervolemia decreases gastroduodenal flow, whereas experimental hypovolemia has the opposite effect (15,16).…”
mentioning
confidence: 99%
“…We have observed that acute BV changes modify the GI motility in anesthetized rats and dogs: gastric and jejunal compliance (9,10), as well as the resistance offered by the gastroduodenal segment to the flow of liquid (11,12). We have also recently extended these observations to the ileocolonic region (15).…”
Section: Discussionmentioning
confidence: 98%
“…In a barostatically perfused system we have also observed, in anesthetized dogs and rats, that the resistance offered by the gastroduodenal (GD) segment to the flow of liquid is modulated by BV levels: BV expansion decreased the GD flow while BV retraction increased it (11,12).…”
Section: Introductionmentioning
confidence: 93%